Silicone Plastination of Nasus and Lingua in Large Ruminants with and without Use of Formaldehyde - Baygeldi, Saime Betul; Ozkan, Zait Ender; Yilmaz, Sadik; Kanmaz, Yesim Aslan (Soc Chilena Anatomia, 2022)
Plastination is an anatomical preparate preparation technique characterized by the replacement of tissue fluids with a reactive polymer. Although more challenging and economically costly than many anatomical methods, this method is desirable because of the fact that specimens created in this method are highly similar to the natural appearance of the intended objects, and they are durable and harmless end products for human health. Our main goal was to completely leave out formaldehyde and similar carcinogenic chemicals used in a method like plastination and to allow production of formaldehyde-free plastinates to be used in anatomy training and examinations in our country. To that end, we compared nose and tongue of 10 large ruminants by subjecting them to plastination, 5 of them with formaldehyde and 5 of them without formaldehyde, and aimed to leave formaldehyde out by taking into account the difference between them. Silicone plastination is the most commonly-used and best-known technique among the plastination techniques because specimens created using this technique look aesthetically impressive. Silicone plastination consists mainly of 5 phases. First of all, we obtained the anatomical situs we wanted and made specimens ready by dissecting some of them after fixation and some of them without fixation. Then, after the implementation of a dehydration phase in acetone baths at-25 degrees C, a forced impregnation phase was implemented by using a mixture of S10-S3 chemical under negative pressure. In the final phase, the curing and hardening phase, the plastination process was completed by giving the specimens their final shape with the use of the S6 solution. As a result, no significant difference was observed between silicone plastination with and without formaldehyde.
Plastinación de Silicona de Nasus y Lengua en Rumiantes Mayores con y sin el Uso de Formaldehido
Keywords: Anatomy; Formaldehyde; Large ruminants; Plastination; Silicone